Sumudu Iterative Method for solving Nonlinear Partial Differential Equations - Aswhad, Asmaa A.; Yassein, Samaher M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2021)
In this paper, we apply a new technique combined by a Sumudu transform and iterative method called the Sumudu iterative method for resolving non-linear partial differential equations to compute analytic solutions. The aim of this paper is to construct the efficacious frequent relation to resolve these problems. The suggested technique is tested on four problems. So the results of this study are debated to show how useful this method is in terms of being a powerful, accurate and fast tool with a little effort compared to other iterative methods.